Review On Layout Optimization For Rollingstock Maintenance Depot - Kartikaningtyas, Dela Safitri; Raharno, Sri; Handoko, Yunendar Aryo (Syntax Literate, 2025)
This review paper discusses the importance of having an optimal layout for rollingstock maintenance depots to optimize rollingstock maintenance in improving maintenance efficiency and reducing maintenance costs while maintaining the availability and reliability of railway vehicles. The current problems in rollingstock maintenance depots faced by railway industry are limited land availability, limited storage space, material handling issues, and the lack of standards for train maintenance depot layouts. The paper also presents classification criteria and categories on layout planning and maintenance optimization approach for rollingstock maintenance depots based on various recent studies including the methods used and the results obtained. Finally, this review paper proposes guidelines for future research on rollingstock maintenance depots in Indonesia as decision-making that considers the economic factors of layout optimization and the implications for safety and the environment of maintenance activities. This could also help improve the company's reputation as well as prepare for future expansion